Quantificação do Coeficiente de Transmissão Térmica de Vãos Envidraçados - Alexandra Félix de Agrela (2011)
The environmental sustainability and reducing energy consumption are more and more important to the building3;s concepcion and rehabilitation. The glazed openings are responsible for a high percentage of the total heat loss of a building. The market for windows has evolved a lot in order to obtain more favorable thermal characteristics.To calculate the building3;s thermal behaviour it3;s fundamental to know the thermal transmittance of windows. There are tabulated values for this coeficient, however, the tables do not include all solutions on the market. The thermal transmittance can still be determined by calculation methods present in European standards, but these are not easy to apply.The use of an automatic calculation program facilitates the determination of this coefficient. Currently there are few programs that determine the calculation of this ratio in a quick and easy way.This work is intended to test an automatic calculation program developed in a Master's thesis, the UWVal by Vitor Mendes, which determines the thermal transmittance of windows using the simplified calculation method of the present European standards. To achieve this, comparisons will be made between the results obtained by this program, the results of an already existing one, the WIS, and the tabulated values present in national documents, in particular ITE50.The influence of several factors in the value of the thermal transmittance of window will also be refered, that is the type of frame, the gas present in the air space of double glazing, the width of the air space in double glazing and still the relation between Aglass/Aframe.KEYWORDS: Energy, thermal transmittance, windows, calculation programs.